2016
DOI: 10.1002/cjce.22646
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of mesoporous silica materials (MCM‐41) using silica fume as the silica source in a binary surfactant system assisted by post‐hydrothermal treatment and its Pb2+ removal properties

Abstract: Mesoporous silica materials (MCM‐41) were successfully prepared by substituting silica fume for silicate in different surfactant systems. The effects of binary surfactant systems and post‐hydrothermal treatment on the morphology and structural properties of MCM‐41 were investigated based on X‐ray diffraction (XRD), N2 sorption/desorption, and transmission electron microscopy analyses (TEM). The results confirmed that polyethylene glycol (PEG‐6000) is an effective additive template in a binary surfactant system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
0
1
0
1
Order By: Relevance
“…[19][20][21] No entanto, vários estudos têm mostrado a utilização de outros materiais ricos em silício (resíduos) na síntese de peneira moleculares. Chiarakorn e colaboradores 22 utilizaram cinza de casca de arroz, Zhou e colaboradores 23 utilizaram silicatos de solos e Zhu e colaboradores 24 utilizaram sílica ativa (microssílica). A sílica biogênica é uma excelente fonte alternativa de sílica para a síntese de peneira molecular por ser uma forma de estrutura amorfa que é mais reativa na reação de formação de silanóis.…”
Section: Introductionunclassified
“…[19][20][21] No entanto, vários estudos têm mostrado a utilização de outros materiais ricos em silício (resíduos) na síntese de peneira moleculares. Chiarakorn e colaboradores 22 utilizaram cinza de casca de arroz, Zhou e colaboradores 23 utilizaram silicatos de solos e Zhu e colaboradores 24 utilizaram sílica ativa (microssílica). A sílica biogênica é uma excelente fonte alternativa de sílica para a síntese de peneira molecular por ser uma forma de estrutura amorfa que é mais reativa na reação de formação de silanóis.…”
Section: Introductionunclassified
“…Mesoporous silica materials (MCM‐41) were successfully prepared by substituting silica fume for silicate in different surfactant systems. Zhu et al confirmed that polyethylene glycol (PEG‐6000) is an effective additive template in a binary surfactant system for the synthesis of mesoporous silica materials . Wu et al studied the mass transfer and reaction kinetics of soybean oil epoxidation using concentrated hydrogen peroxide in a formic acid‐autocatalyzed reaction system, and then they developed a biphasic model for the epoxidation process .…”
mentioning
confidence: 99%